54.0k views
1 vote
9) Solve: a^2+ b^2= c^2 for b

User Sidyll
by
5.8k points

2 Answers

3 votes

Answer:

b = ±√(c² - a²)

Explanation:

We have to get the value of B.

Step 1: (b squared = c squared - a squared)

b² = c² - a²

Step 2: (cube root of b squared = cube root of c squared and a squared)

√b² = √(c² - a²)

We get the answer as:

b = ±√(c² - a²)

User Nicholas Graham
by
5.2k points
2 votes

Answer:

  • b = ±√(c² - a²)

Explanation:

Given equation

  • a²+ b²= c²

Solving for b:

  • b² = c² - a²
  • √b² = √(c² - a²)
  • b = ±√(c² - a²)
User Valeen
by
5.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.